Breast Reduction in Adults: Identifying Risk Factors for Overall 30-Day Postoperative Complications. (7th July 2020) - Aravind, Pathik; Siotos, Charalampos; Bernatowicz, Elizabeth; Cooney, Carisa M; Rosson, Gedge D
Abstract: Background: Breast reduction is a commonly performed procedure. Understanding the postoperative complication profile is important for preoperative planning and patient education. Objectives: The authors sought to assess complication rates following breast reduction in females and identify potential risk factors. Methods: We assessed the records of the American College of Surgeons National Surgical Quality Improvement Program participant use files that include patients who underwent breast reduction for macromastia between 2005 and 2016. Relevant patient and postoperative data were extracted, and factors affecting complications were analyzed utilizing the logistic regression model. Results: We identified 20, 001 women aged a mean 43.9 years who underwent breast reduction. The number of patients who developed ≥1 complication was 1009 (4.3%). Our adjusted analysis revealed that outpatient setting (odds ratio [OR] = 0.600) and performance of the surgery by the attending surgeon alone (OR = 0.678) were associated with lower odds, whereas higher body mass index (OR = 1.046) and smoking (OR = 1.518) were associated with higher odds for complications following breast reduction. Outpatient setting (OR = 0.317) was also associated with lower odds whereas smoking (OR = 1.613) and American Society of Anesthesiologists class were associated with higher odds of returning to the operative room. These findings were consistent in our subgroup analysis for wound-related complications. Conclusions: Our study shows that patient characteristics such as smoking and body mass index may increase complication rates after breast reduction. Clinical factors such as inpatient setting may also increase risk of complications following breast reduction. It is critical to understand the effect of these factors to better predict postoperative outcomes and ensure thorough patient education.